The Impacts Of Covid-19 To Saudi Arabia’s Economic Sector And Hajj Pilgrimage Policy Of The Kingdom Of Saudi Arabia - et. al., Gilang Nur Alam, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Saudi Arabia is a state located in the Middle East, which is apart from being one of the largest oil producers in the world, is also the prime destination of religious tourism for Muslims worldwide. Due to the COVID-19 pandemic, all activities in Saudi Arabia have stopped, including Umrah and Hajj pilgrimage. This condition is exacerbated by the fall of the world’s oil price that led to a drop in public revenues for the country. In this research, the authors will use the theory of Mercantilism as well as using the qualitative method with the explanatory approach and secondary data to review the case. The findings of this article found that COVID-19 makes an impact on both the economy and religious tourism in Saudi Arabia.